The effect of legume cover crops grown in an olive orchard on soil microbial activity - Pereira, Ermelinda (2013)
Microbial biomass and soil respiration are major indicators of the soil biological fertility which can be affected by soil management practices. The aim of this study was the evaluation of the effect of three ground-cover treatments, imposed to an olive orchard, on soil microbial biomass and activity. The ground-cover treatments were: Natural vegetation (Nat veg); Natural vegetation fertilized with 60 kg N ha-1 (Nat veg +N); and a mixture of eleven sdf-reseed.ing annual legumes (Legumes) grown as a cover crop. The experiment was carried out in a rainfed olive orchard located in Mirandela, NE Portugal. Three years after the experimental set-up had been installed, random samples of soil were collected in two depths, 0-10 cm and 10-20 cm. The microbial biomass C (Cmic) was determined by the fumigation-extraction method; the basal respiration (BR) as the rate of C02 eyolved in a 7 days soil incubation at 25 oc; and soil organic C (Corg) by the Walkley-Black method. The Cmic:Corg ratio and the metabolic quotient (qCOz.), defined as the respiration rate per unit of biomass, were thereafter estimated. The values of Cmic and BR were significandy higher under the Legumes treatment in comparison with Nat veg +N and Nat veg. It seems that Legumes increased the C stored in the soil and promoted soil microbial activity, two soil quality factors usually related to the sustainability of the agrosystems.